Centros de Informação em Saúde Popular : construção de um referencial teórico - Matsuno, Graziella Yuri (2016)
This study aims to build a theoretical framework that embase the proposal, creation and implementation of a People's Health Information Center in public libraries and third sector organizations in the communities with socioeconomic vulnerability in São Carlos (SP) and the region as a public communication channel of science among the population through the dissemination and popularization of scientific library collections and information services. This information unit is designed based on the existing literature theory about People's Documentation Centers. The focus of this work is the health information, specifically information on popular health and alternative medicine. Moreover, the epistemological stance advocated to guide the professional practice and librarian policy stance should act on in Popular Health Information Centres follows the ideological line of the Popular Education movement of Paulo Freire, as well as the concept of "organic intellectual" of Antonio Gramsci. Finally are listed some spaces and contexts considered favorable and suitable for the application and development of the proposal. It also points up some theories and methodologies that would be advisable to start a research work of information needs in community health to be met by the Centre.